2012
DOI: 10.1159/000343775
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of Recombinant Human Epidermal Growth Factor and Basic Fibroblast Growth Factor on Corneal Epithelial Wound Healing and Neovascularization in vivo and in vitro

Abstract: Purpose: This study was undertaken to investigate the effects of recombinant human epidermal growth factor (rhEGF) and basic fibroblast growth factor (bFGF) on corneal wound healing and neovascularization (CNV). Methods: The positive effects of 10 ng/ml rhEGF and bFGF on the proliferation of corneal epithelial cells (SD-HCEC1s), rabbit keratocyte cells (RKCs) and human umbilical vein endothelial cells (HUVECs) as well as the effects on the migration capacity on HUVECs were observed. An animal central corneal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 54 publications
2
33
0
3
Order By: Relevance
“…Very recent studies showed that the application of growth factors could suppress CNV in animal models [14,15]. In the present study, we developed a different approach by employing RNAi-mediated knockdown of CXCR4 and CXCR7 in RF/6A cells.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies showed that the application of growth factors could suppress CNV in animal models [14,15]. In the present study, we developed a different approach by employing RNAi-mediated knockdown of CXCR4 and CXCR7 in RF/6A cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the number of fibroblasts primarily arise due to the proliferation of resident fibroblasts in response to growth factors, including bFGF, and fibroblasts migrating from the surrounding connective tissue into the wound site (40). It was observed that recombinant bFGF accelerates the wound healing process (14,41), thus, rb-bFGF was used as a positive control for MEBO. In the current study, rb-bFGF promoted the formation of granulation tissue, increased neovascularization and the number of fibroblasts in the granulation tissue, and reduced the time of wound healing, which were all consistent with the effects of MEBO.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, rb-bFGF promoted the formation of granulation tissue, increased neovascularization and the number of fibroblasts in the granulation tissue, and reduced the time of wound healing, which were all consistent with the effects of MEBO. It is generally accepted that VEGF induces endothelial cell proliferation and migration, promotes vascular permeability and angiogenesis, increases collagen deposition (5,(9)(10)(11), and that bFGF mediates angiogenesis, promotes the proliferation and migration of endothelial cells and fibroblasts proliferate and migration (12)(13)(14)(15)42). Therefore, it was inferred that MEBO promotion of wound healing in rats involves growth factors, including VEGF and bFGF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations